Assessment of oral and dental health status in children with cerebral palsy: An exploratory study - Sedky, Nabila A. (International Journal of Health Sciences, 2018)
Objectives: Evaluating oral and dental health status in Egyptian children with cerebral palsy in relation to gross motor skills and types of CP. Methods: Cross-sectional study was conducted at el-Shatby Hospital for Children, Alexandria-Egypt. Oral examination for 62 children with CP between the age ranges 3–12 years was performed and DMFT/dft, OHI-S and MGI indices were charted. Maxillofacial defects, dental problems and drooling of saliva were assessed. Children's CP type, motor milestone and gross motor skills were determined. All statistical analyses were carried out at p<0.05 and 0.01. Results: About 84.0% of children had spastic quadriplegia, 41.9% were sit supported, 32.3% had Level IV GMFCS, and 29.0% had Level V. No maxillofacial defects, 14.5% had dentine exposure greater than 1/3 of the surface, 22.6% had frequent/severe drooling saliva. Caries prevalence comprised 54.8%, 53.2% had poor oral hygiene (OHI-S Index) and 43.6% had severe gingival inflammation (MGI Index). The first best predictor variable for dft was “Motor Milestone”. GMFCS (Level IV and V) was the first best predictor variable for DMFT, OHI-S and MGI Indices. Conclusion: The majority of children had dental caries, poor oral hygiene and severe gingival inflammation. Children who were sit supported, had no neck support and stand supported were suffering from dental caries (dft) more than children who were sitting and walking alone. Children with Levels IV/V GMFCS were prone to have dental caries (DMFT), susceptible to suffer from bad oral hygiene, and older children experiencing severe gingivitis more than younger ones.